(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The goal of developing emotional-communicative competence in students of higher medical schools is to increase their ability to communicate effectively with patients, families and medical professionals. This includes developing skills related to emotional intelligence, empathy, active listening and effective communication strategies. By improving their emotional and communicative competence, students can develop better relationships with patients, understand their emotional needs, and provide more patient-centered care. In addition, the development of emotional and communicative competence can lead to improved teamwork, increased job satisfaction, and reduced stress among healthcare workers. In general, the goal of developing emotional and communicative competence in medical students is to produce competent and compassionate healthcare professionals who can provide quality care to their patients.